Pengaruh Pemberian Jus Buah Naga Merah (Hylocereus Polyrhizus) terhadap Tekanan Darah pada Masyarakat di Wilayah Puskesmas Pembantu Desa Paku (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Elevated blood pressure above the normal range is a hallmark of a medical condition known as hypertension. It is estimated that as the population ages, the number of hypertension cases will also increase. If this condition is properly managed early, it can be controlled. Controlling daily eating habits is one of the most effective non-pharmacological methods for lowering blood pressure. Therefore, finding alternative food sources that can naturally lower blood pressure is crucial. Red dragon fruit (Hylocereus polyrhizus), which is high in fiber, potassium, and antioxidants such as vitamins B, C, and E, is one possible option. These nutrients are important for maintaining blood vessel flexibility and controlling hypertension. The purpose of this study was to determine the effect of red dragon fruit juice consumption on blood pressure in the Paku Village Community Health Center (Puskesmas Pembantu) operational area. A single-group pre-experimental design was used in this study. A paired-sample t-test was used to assess the data. Based on the findings, the average systolic blood pressure was 184 mmHg before consuming red dragon fruit juice and decreased to 164 mmHg after the intervention. With a t-value of 23.4, a correlation of 0.96, and a p-value of 0.000 (p < 0.05), this decrease was statistically significant. Meanwhile, the average diastolic blood pressure dropped from 101 mmHg to 84 mmHg, with a correlation of 0.961, a t-value of 18.65, and a p-value of 0.000 (p < 0.05). These results indicate that consuming red dragon fruit juice significantly lowers blood pressure, with an average decrease in systolic pressure of 20 mmHg and diastolic pressure of 17 mmHg.